Histone deacetylase inhibitors valproic acid and vorinostat enhance trastuzumab-mediated antibody-dependent cell-mediated phagocytosis. Issue 1 (2nd January 2020) - Laengle, Johannes; Kabiljo, Julijan; Hunter, Leah; Homola, Jakob; Prodinger, Sophie; Egger, Gerda; Bergmann, Michael
Abstract : Background: The monoclonal antibody (mAb) trastuzumab is part of the standard of care for patients with human epidermal growth factor receptor 2 (HER2)-overexpressing breast cancer. Antibody-dependent cell-mediated phagocytosis (ADCP) and cytotoxicity (ADCC) are major mechanisms of action of the mAb trastuzumab. Histone deacetylase inhibitors (HDACi), such as valproic acid (VPA) or vorinostat (SAHA), exert several immunostimulatory properties, which contribute at least in part to their anticancer effect. However, the impact of HDACi-induced immunostimulatory effects on trastuzumab-mediated anti-tumor immune response is not well characterized. Methods: We analyzed the ADCP and ADCC activity of peripheral blood mononuclear cells (PBMCs) from age and gender-matched healthy volunteers (n=5) against HDACi-treated HER2-overexpressing breast cancer cells (SKBR3), using a well-established in vitro three-color imaging flow cytometry and flow cytometry approach. Results: VPA and SAHA enhanced trastuzumab-mediated ADCP and trastuzumab-independent cytotoxicity. Mechanistically, VPA upregulated the activating antibody-binding receptor Fc-gamma receptor (FcγR) IIA (CD32A) on monocytes (CD14+). Moreover, VPA and SAHA downregulated the anti-apoptotic protein myeloid leukemia cell differentiation 1 (MCL1) in breast cancer cells. Additionally, VPA and SAHA induced an immunogenic cell death, characterized by the exposure of calreticulin (CALR), as well as decreased the "do not eat me" signal CD47 on tumor cells. Conclusions: HDACi VPA and SAHA increase trastuzumab-mediated phagocytosis and trastuzumab-independent cytotoxicity. The immunomodulatory activities of those HDACi support a rationale combined treatment approach with mAb for cancer treatment.